Allogeneic Bone Marrow-Derived Mesenchymal Stromal Cells Promote Healing of Refractory Perianal Fistulas in Patients With Crohn's Disease - Molendijk, Ilse; Bonsing, Bert A; Roelofs, Helene; Peeters, Koen C M J; Wasser, Martin N J M; Dijkstra, Gerard; van der Woude, C Janneke; Duijvestein, Marjolijn; Veenendaal, Roeland A; Zwaginga, Jaap-Jan; Verspaget, Hein W; Fibbe, Willem E; et al. (Gastroenterology (New York, N.Y. 1943), 2015)
Patients with perianal fistulizing Crohn's disease have a poor prognosis because these lesions do not heal well. We evaluated the effects of local administration of bone marrow-derived mesenchymal stromal cells (MSCs) to these patients from healthy donors in a double-blind, placebo-controlled study. Twenty-one patients with refractory perianal fistulizing Crohn's disease were randomly assigned to groups given injections of 1 × 10(7) (n = 5, group 1), 3 × 10(7) (n = 5, group 2), or 9 × 10(7) (n = 5, group 3) MSCs, or placebo (solution with no cells, n = 6), into the wall of curettaged fistula, around the trimmed and closed internal opening. The primary outcome, fistula healing, was determined by physical examination 6, 12, and 24 weeks later; healing was defined as absence of discharge and <2 cm of fluid collection-the latter determined by magnetic resonance imaging at week 12. All procedures were performed at Leiden University Medical Center, The Netherlands, from June 2012 through July 2014. No adverse events were associated with local injection of any dose of MSCs. Healing at week 6 was observed in 3 patients in group 1 (60.0%), 4 patients in group 2 (80.0%), and 1 patient in group 3 (20.0%), vs 1 patient in the placebo group (16.7%) (P = .08 for group 2 vs placebo). At week 12, healing was observed in 2 patients in group 1 (40.0%), 4 patients in group 2 (80.0%), and 1 patient in group 3 (20.0%), vs 2 patients in the placebo group (33.3%); these effects were maintained until week 24 and even increased to 4 (80.0%) in group 1. At week six, 4 of 9 individual fistulas had healed in group 1 (44.4%), 6 of 7 had healed in group 2 (85.7%), and 2 of 7 had healed in group 3 (28.6%) vs 2 of 9 (22.2%) in the placebo group (P = .04 for group 2 vs placebo). At week twelve, 3 of 9 individual fistulas had healed in group 1 (33.3%), 6 of 7 had healed in group 2 (85.7%), 2 of 7 had healed in group 3 (28.6%), and 3 of 9 had healed in the placebo group (33.3%). These effects were stable through week 24 and even increased to 6 of 9 (66.7%) in group 1 (P = .06 group 2 vs placebo, weeks 12 and 24). Local administration of allogeneic MSCs was not associated with severe adverse events in patients with perianal fistulizing Crohn's disease. Injection of 3 × 10(7) MSCs appeared to promote healing of perianal fistulas. ClinicalTrials.gov ID NCT01144962.